Transcriptomic Features of T Cell-Barren Tumors Are Conserved Across Diverse Tumor Types - Routh, Eric D.; Pullikuth, Ashok K.; Jin, Guangxu; Chifman, Julia; Chou, Jeff W.; D'Agostino, Ralph B.; Seino, Ken-ichiro; Wada, Haruka; Print, Cristin G.; Zhang, Wei; Lu, Yong; Miller, Lance D. (Frontiers in Immunology, 2020)
Background: Understanding how tumors subvert immune destruction is essential to the further development of cancer immunotherapies. New evidence suggests that tumors limit anti-tumor immunity by exploiting transcriptional programs that regulate intratumoral trafficking and accumulation of effector cells. Here, we investigated the gene expression profiles that distinguish immunologically “cold” and “hot” tumors across diverse tumor types. Methods: RNAseq profiles of tumors (n=8,920) representing 23 solid tumor types were analyzed using immune gene signatures that quantify CD8+ T cell abundance. Genes and pathways associated with a low CD8+ T cell infiltration profile (CD8-Low) were identified by correlation, differential expression and statistical ranking methods. Gene subsets were evaluated in immunotherapy treatment cohorts and functionally characterized in cell lines and mouse tumor models. Results: Among different cancer types, we observed highly significant overlap of genes enriched in CD8-Low tumors, which included known immunomodulatory genes (e.g., BMP7, CMTM4, KDM5B, RCOR2) and exhibited significant associations with Wnt signaling, neurogenesis, cell-cell junctions, lipid biosynthesis, epidermal development and cancer-testis antigens. Analysis of mutually-exclusive gene clusters demonstrated that different transcriptional programs may converge on the T-cell cold phenotype as well as predict for response and survival of patients to nivolumab treatment. Furthermore, we confirmed that a top-ranking candidate belonging to the TGF-β superfamily, BMP7, negatively regulates CD8+ T cell abundance in immunocompetent murine tumor models, with and without anti-PD-L1 treatment. Conclusions: This study presents first evidence that solid tumors of diverse anatomical origin acquire conserved transcriptional alterations that may be operative in the T cell-cold state. Our findings demonstrate the potential clinical utility of CD8-Low tumor-associated genes for predicting patient immunotherapy outcomes and point to novel mechanisms with potential for broad therapeutic exploitation.